MSC-Derived Extracellular Vesicles to Heal Diabetic Wounds: a Systematic Review and Meta-Analysis of Preclinical Animal Studies - Bailey, Adrian J. M. (Stem Cell Rev Rep, 2021)
INTRODUCTION: Extracellular vesicles from mesenchymal stromal cells (MSC-EVs) have shown promise in wound healing. Their use in diabetic wounds specifically, however, remains pre-clinical and their efficacy remains uncertain less clear. A systematic review of preclinical studies is needed to determine the efficacy of MSC-EVs in the treatment of diabetic wounds to accelerate the clinical translation of this cell-based therapy. METHODS: PubMed and Embase were searched (to June 23, 2020). All English-language, full-text, controlled interventional studies comparing MSC-EVs to placebo or a “no treatment” arm in animal models of diabetic wounds were included. Study outcomes, including wound closure (primary outcome), scar width, blood vessel number and density, and re-epithelialisation were pooled using a random effects meta-analysis. Risk of bias (ROB) was assessed using the SYRCLE tool for pre-clinical animal studies. RESULTS: A total of 313 unique records were identified from our search, with 10 full text articles satisfying inclusion criteria (n = 136 animals). The administration of MSC-EVs improved closure of diabetic wounds compared to controls with a large observed effect (Standardized Mean Difference (SMD) 5.48, 95% Confidence Interval (CI) 3.55–8.13). Healing was further enhanced using MSC-EVs enriched in non-coding RNAs or microRNAs compared to controls (SMD 9.89, 95%CI 7.32–12.46). Other outcomes, such as blood vessel density and number, scar width, and re-epithelialisation were improved with the administration of MSC-EVs, with a large effect. ROB across studies was unclear. CONCLUSION: MSC-EVs, particularly following enrichment for specific RNAs, are a promising treatment for diabetic wounds in pre-clinical studies and translation to the clinical domain appears warranted. REGISTRATION: PROSPERO #CRD42020199327 [248]. GRAPHICAL ABSTRACT: [Figure: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12015-021-10164-4.